Triple Entry Bookkeeping di Era Teknologi Blockchain: Suatu Kajian Literatur - Arisona Ahmad; Ika Sri Wahyuni; Lailatul Istiqomah; Eka Wulan Wahyuning Tiyas (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
The financial industry in the era of technological development began to be supported by Blockchain technology. Blockchain is a new idea in the financial industry as a solution to solve the problem of digital money (cryptocurrency). Transactions recorded in the blockchain will be permanently stored so that they cannot be manipulated and provide a higher level of security. Blockchain technology supports the development of triple entry bookkeeping which is a configuration of the development of the double entry bookkeeping system. This research uses qualitative proximity to the library research method. The data collected comes from indexed journals on Google Scholar, Science and Technology (Sinta), Directory of Open Access Journals (DOAJ), books and other literature which will then be analyzed and set forth in the form of written words.The results of this study show that Triple Entry Bookkeeping in the Blockchain era has many advantages as a form of development of Double Entry Bookkeeping, namely providing information about budgets, automatic transaction validation, automatic public ledger, increasing openness & trust, and solving fraud. In Indonesia itself, blockchain implementation in the field of accounting has been widely carried out, such as on the Online Pajak platform, Bank BCA, PT Pos Indonesia, and other commercial companies listed on the Indonesian Blockchain Association (ABI). The implementation of the triple entry bookkeeping system is still not ready to be implemented by medium-sized entities and MSMEs due to the high costs required, the lack of understanding of professional accountants regarding technology and entities that feel they still do not need a triple entry bookkeeping system. Therefore, support from all parties is needed so that this research can develop and not only become a concept but can be implemented in the financial industry.